2015
DOI: 10.1016/j.hkjot.2015.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Written and Pictorial Home Exercise Prescription on Adherence for People with Stroke

Abstract: Background/Objective: Functional recovery for stroke survivors begins with rehabilitation. It may not be feasible for therapists to supervise all rehabilitation, especially in the home environment. Therefore, adherence to prescribed exercise programmes is important. The objective of this study was to determine the effect of a written and pictorial home exercise prescription on adherence to a home exercise programme in patients with stroke. Methods: This was a randomised controlled trial with a blinded assessor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…South African physiotherapy stroke rehabilitation research is undertaken to establish interventions that are context-specific, taking into consideration available resources (human and material), geographical and political factors that are unique to the country or even specific provinces, and we report this research below (Comley-White, Mudzi & Musenge 2018; Kara & Ntsiea 2015; Knox, Stewart & Richards 2018; Mudzi, Stewart & Musenge 2012b; Ntsiea et al 2015; Puckree & Naidoo 2014; Van Wyk 2016; Van Wyk, Eksteen & Rheeder 2014). We also have included intervention evidence from studies conducted outside South Africa whose findings we consider are relevant to the SA context.…”
Section: Resultsmentioning
confidence: 99%
“…South African physiotherapy stroke rehabilitation research is undertaken to establish interventions that are context-specific, taking into consideration available resources (human and material), geographical and political factors that are unique to the country or even specific provinces, and we report this research below (Comley-White, Mudzi & Musenge 2018; Kara & Ntsiea 2015; Knox, Stewart & Richards 2018; Mudzi, Stewart & Musenge 2012b; Ntsiea et al 2015; Puckree & Naidoo 2014; Van Wyk 2016; Van Wyk, Eksteen & Rheeder 2014). We also have included intervention evidence from studies conducted outside South Africa whose findings we consider are relevant to the SA context.…”
Section: Resultsmentioning
confidence: 99%
“…The entire CogGym platform interface is in Arabic language. CogGym contains ten sub-games that are used to enhance the ten different perceptions capabilities for each person as addressed in literature (Lin et al, 2012;Malinowsky et al, 2015;Kara and Ntsiea, 2015;Rubrics and Fun, 2018) that are defined in Table 1. Visual discrimination is defined as the capability to recognise differences and similarities between size, shapes, colours, patterns and objects.…”
Section: Coggym Specification and Descriptionmentioning
confidence: 99%
“…Yearly, millions of critically ill patients experience newly acquired long-term cognitive impairment and major physical, mental and functional disabilities (Jackson et al, 2012;Kara and Ntsiea, 2015). Those patients are given the diagnosis of post-intensive care syndrome (PICS).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, for continuation of exercise training program, physiotherapists would prescribe home exercises programs in paper-based format. 9,10 However, evidence showed that home exercise prescription in paper-based format does not lead to better adherence to a home exercise program compared to having no written and pictorial instructions for patients with stroke less than four months. 10 The recent increasing accessibility of smart technology 11 o®ers an opportunity to advance the mode of delivery of home exercise program by mobile devices such as video-guided exercise on electronic tablets 12 and video-guided exercise on mobile apps.…”
Section: Introductionmentioning
confidence: 99%
“…12 In contrast, another study showed that people with musculoskeletal conditions who adhere better to their home exercise programs in video-based format are provided with an app with remote support compared to paper handouts; although the clinical importance of this added adherence is unclear. 13 Since one of the major outcomes to evaluate the e®ectiveness of the mode of delivery of home exercise program is adherence, 10,12,13 it is worthwhile to study the factor a®ecting adherence of mode of delivery of home exercise program. It was suggested that one of the barriers to adherence of home exercise is low self-e±cacy.…”
Section: Introductionmentioning
confidence: 99%